The Relationship between Environmental Knowledge and Sport Event Organizers' Support for Sustainable Management in Sport - Leila Nazari; Keivan Shabani Moghaddam (New Approaches in Sport Sciences)
The purpose of the present study was to investigate the relationship between environmental knowledge and sport event organizers' support for sustainable management in sport. The present study is a descriptive-survey and field study. In order to collect data, a researcher-made questionnaire with 40 questions was used. The face and content validity of the questionnaire was confirmed by a survey of professors related to the research topic. The construct validity was confirmed by confirmatory factor analysis of more than 0.3 and its reliability was confirmed byCronbach's alpha of 0.83. The statistical population of the study consisted of managers and organizers of sport events in ten provinces of the country with approximately 1000 peope. The sample size was 278 according to Morgan table, Due to the size, number and difficulty of access, the available sampling method was used to collect the samples and finally 254 questionnaires were returned. Data analysis was performed using SPSS-19 software. The results showed that the level of environmental awareness in the sample was in the range of 0 to 8 and the mean of the total sample was 3.55 with a standard deviation of 1.61. These results indicate a low level of awareness of environmental issues in the sample under study. In the present study, it seems that there is little awareness of environmental issues that may be effective in shaping people's attitudes toward the intention to support environmental issues in sporting events. Since human attitudes are driven by consciousness, it is therefore necessary to change attitudes by providing a context for raising awareness and enabling appropriate behavior. Therefore, determining the level of knowledge and attitude of individuals is the first step in determining and delivering educational programs.